The supervised learning workshop a new, interactive approach to understanding supervised learning algorithms - Bateman, Blaine; Jha, Ashish Ranjan; Johnston, Benjamin; Mathur, Ishita (Packt, 2020)
bCut through the noise and get real results with a step-by-step approach to understanding supervised learning algorithms/b h4Key Features/h4 ulliIdeal for those getting started with machine learning for the first time /li liA step-by-step machine learning tutorial with exercises and activities that help build key skills /li liStructured to let you progress at your own pace, on your own terms /li liUse your physical print copy to redeem free access to the online interactive edition/li/ul h4Book Description/h4 You already know you want to understand supervised learning, and a smarter way to do that is to learn by doing. The Supervised Learning Workshop focuses on building up your practical skills so that you can deploy and build solutions that leverage key supervised learning algorithms. You'll learn from real examples that lead to real results. Throughout The Supervised Learning Workshop, you'll take an engaging step-by-step approach to understand supervised learning.